THE DEVELOPMENT OF METHODOLOGY FOR EMPIRICAL STUDIES OF THE SOCIODYNAMICS OF CORPORATE VALUES: NETWORK MEASUREMENT - P. P. Deriugin; I. A. Baruzdin; A. S. Taranenko; M. V. Sivokon (Дискурс)
The article focuses on examination and analysis of the experience of building the methodology of empirical research of corporate values. Previous studies have shown the need to improve the system of parameters which describe the network characteristics of corporate values. To study the sociodynamics of corporate values, network parameters are used, such as weight, density, scope, and significant weights. These parameters, traditional for such studies, are supplemented by another one, as the parameter of value potential is proposed for discussion. Empirical research is carried out on three objects, which are two corporations at different stages of their formation and the respondents of the surrounding society. The results obtained in the course of empirical research are then discussed with experts allowing to verify the value potential parameter as adequate. In essence, this parameter can be described as the importance and strength of the value network. Comparing value networks of different corporations using this parameter allows us to talk about the advantages of some networks over others. These conclusions are particularly important for practical work.